Assessment of AlZnMgCu alloy powder modification for crack-free laser powder bed fusion by differential fast scanning calorimetry. (June 2021) - Zhuravlev, Evgeny; Milkereit, Benjamin; Yang, Bin; Heiland, Steffen; Vieth, Pascal; Voigt, Markus; Schaper, Mirko; Grundmeier, Guido; Schick, Christoph; Kessler, Olaf
Graphical abstract: Highlights: Rapid melting and solidification of single Aluminium alloy 7075 powder particles have been analysed by Differential Fast Scanning Calorimetry (DFSC). Surface inoculation with TiC nanoparticles of Aluminium alloy 7075 powder particles decreased undercooling and scatter of undercooling during rapid solidification. Hot cracking during Laser Powder Bed Fusion (LPBF) of 7075 was virtually eliminated by surface inoculation with TiC nanoparticles. The powder modification successful in LPBF showed the lowest solidification undercooling and smallest scatter of undercooling in DFSC. DFSC thus allows an initial powder assessment on tiny amounts of powder, reducing the effort of trial and error in LPBF. Abstract: Additive manufacturing, e.g. by laser powder bed fusion (LPBF), is very attractive for lightweight constructions, as complex and stress-optimised structures integrating multiple functions can be produced within one process. Unfortunately, high strength AlZnMgCu alloys tend to hot cracking during LPBF and thus have not so far been applicable. In this work the melting and solidification behaviour of AlZnMgCu alloy powder variants with particle surface inoculation was analysed by Differential Fast Scanning Calorimetry. The aim is to establish a method that makes it possible to assess powder modifications in terms of their suitability for LPBF on a laboratory scale requiring only small amounts of powder. Therefore, solidification undercooling is evaluated at cooling rates relevant for LPBF. A method for the temperature correction and normalisation of the DFSC results is proposed. Two ways of powder modification were tested for the powder particles surface inoculation by titanium carbide (TiC) nanoparticles: via wet-chemical deposition and via mechanical mixing. A low undercooling from DFSC correlates with a low number of cracks of LPBF-manufactured cubes. It appears that a reduced undercooling combined with reduced solidification onset scatter indicates the possibility of crack-free LPBF of alloys that otherwise tend to hot cracking.